ANALISIS PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN PRODUK MELALUI ONLINE SHOP - Yanti, Aprilda; Syahab, Muhammad Asyari (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Competition in business activities is something that definitely exists, especially since the flow of globalization is increasingly unstoppable, which will create conditions for tighter competition. For those who are not sensitive, it is certain that this business will not last long. This competition also provides opportunities and challenges. Those who are sensitive to environmental changes always try to find the best way to capture and maintain market share. This research was conducted to see consumer behavior before making a purchase until finally deciding to purchase a product. The method in this research is a descriptive method using a qualitative approach, data collection techniques using interviews, observation and documentation using primary and secondary data. The research results show: (1) Marketing stimuli that encourage consumers to shop online because the products are complete and practical, low prices, fast delivery; (2) Characteristics of individuals who follow online shopping trends, influence from friends, busy, easy to compare prices and products, buy for resale, don't know the location of the shop, and dropship; (3) Online purchasing decisions for product selection are based on reviews, low prices and total sales. Store selection is based on store reputation/rating, response speed, and store location. The time of purchase is often made when there is a promotion and the date when the salary is received. The majority of purchases are more than one, to save on shipping costs. The most common payment method is using a virtual account/transfer, via Alfamart, Indomaret, post office, JNE office and in cash when the goods are received.